2022
DOI: 10.3390/ijms23147952
|View full text |Cite
|
Sign up to set email alerts
|

Neurobiological Mechanisms Modulating Emotionality, Cognition and Reward-Related Behaviour in High-Fat Diet-Fed Rodents

Abstract: Affective and substance-use disorders are associated with overweight and obesity-related complications, which are often due to the overconsumption of palatable food. Both high-fat diets (HFDs) and psychostimulant drugs modulate the neuro-circuitry regulating emotional processing and metabolic functions. However, it is not known how they interact at the behavioural level, and whether they lead to overlapping changes in neurobiological endpoints. In this literature review, we describe the impact of HFDs on emoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 193 publications
0
1
0
Order By: Relevance
“…The effect on cognition in rodents exposed for a long period to an HFD remains debatable, and differences may be considered by diet composition, time of exposure, age and gender of the animals, and/or genetic differences between individual specimens [40][41][42][43][44][45][46]. According to the reported findings in rodent strains, the strong effects of HFD treatment on cognitive performance were observed in both young and adolescent animals; however, a small number of studies employed adult animals [47].…”
Section: Discussionmentioning
confidence: 99%
“…The effect on cognition in rodents exposed for a long period to an HFD remains debatable, and differences may be considered by diet composition, time of exposure, age and gender of the animals, and/or genetic differences between individual specimens [40][41][42][43][44][45][46]. According to the reported findings in rodent strains, the strong effects of HFD treatment on cognitive performance were observed in both young and adolescent animals; however, a small number of studies employed adult animals [47].…”
Section: Discussionmentioning
confidence: 99%
“…In accordance with the developmental origins of health and disease, early-life environmental exposures, such as maternal diet, can enhance the probability and gravity of health concerns in their offspring in the future ( Barker, 2007 ; Armitage et al, 2008 ). The preclinical studies suggest a relationship between maternal high-fat diet (HFD) and neuropsychiatric disorders including autism spectrum disorders ( Gawlińska et al, 2021a , c ), cognitive impairment ( Ziemens et al, 2022 ; Smaga et al, 2023 ), schizophrenia ( Sarker et al, 2019 ), depression ( Giriko et al, 2013 ; Gawlińska et al, 2020b ; Gawliński et al, 2021 ), and substance use disorder ( Gawliński et al, 2020 ). Some investigators also showed that maternal HFD reduces social interactions and increases repetitive behavior ( Ergaz et al, 2016 ; Gawlińska et al, 2020b , Gawlińska et al, 2021c ), as well as evokes the disturbances in short-term memory ( Smaga et al, 2023 ), social memory and sensorimotor gating deficits ( Bordeleau et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%